Performance assessment for irrigation water management: A case study in the Karacabey irrigation scheme in Turkey (International Journal of Irrigation and Water Management, 2015)
The objective of this study is to assess the performance of irrigation water management of the Bursa– Karacabey irrigation scheme (KIS) located in the western Turkey. The study was carried out in two stages. In the first stage, performance of irrigation water management was assessed using two physical and three financial performance indicators for six years during the period 2002–2007. According to the results, the physical performance indicators, which are average irrigation ratio and relative water supply, were found to be 61% and 0.77, respectively. Nevertheless, the financial performance indicators, which are the effectiveness of fee collection, the financial self sufficiency of fees collected to cover management, operating and maintenance budgets, and the staffing number per unit area were found as average 103%, 0.94 and 0.003 persons/ha, respectively. In the second stage, the irrigation water management was tested and assessed by the Logit model taking farmers perceptions concerning satisfaction with taking irrigation service. The probability of the satisfaction in irrigation fee policy and maintenance of irrigation and drainage canals was significant at 0.01 and 0.05 levels, respectively. Most of participants (80%) who use water from the KIS have been satisfied with taking service from the Karacabey Water Users’ Association. According to the research results, it may be claim that the management with regard to physical performance was negative; on the other hand, the management with regard to financial performance and water user satisfaction was positive.